Accuracy of Compensation and Competency Improvement in Improving Performance, Knowledge Sharing as An Intervening Variable - Ahmad Syarifudin Anshori; Moh. Mukhsin; Indra Suhendra; Didit Haryadi (Institute of Computer Science (IOCS), 2022)
An effective performance management system ensures that there is a continuous process to improve performance through the setting of individual and team goals that are aligned with the strategic objectives of the organization. This study examines the compensation system variables, knowledge-sharing competence and employee performance. This research was conducted at Al-Hasyimiyah Modern Islamic Boarding School, Cilegon City, Banten, Indonesia, with a sample of 85 respondents. Data collection methods include a questionnaire using an interval scale of 1 strongly disagree to 10 strongly agree. The data was collected and then analyzed using SEM PLS. The results showed a significant positive effect of providing a compensation system on employee performance. There is a significant positive effect of competence on employee performance. A significant positive effect of providing a compensation system on knowledge sharing is significant. There is a significant positive effect of competence on employee performance. Thus, knowledge sharing has a positive and significant effect on employee performance. To improve employee performance, it is necessary to do, among other things, the accuracy of providing a compensation system, increase competence and implement knowledge sharing effectively.